Crushing behavior and failure modes of kenaf fibre-reinforced composite hexagonal tubes - Alkbir, Munir Faraj Almabrouk (2016)
This research focused on the crashworthiness characteristics of kenaf fibre reinforced composite hexagonal tubes with a variety of configurations. A series of experiments were carried out for composite hexagonal tubes with a different dimension. A hand lay-up technique was used to fabricate the specimens of composite hexagonal tubes Four phases were performed for crushing behaviour, failure mode and crashworthiness parameters of hexagonal composite tubes.The first phase was to study the effect of fibre content on the crashworthiness parameters (i.e, energy absorption and stroke efficiency) and the failure modes of a non-woven kenaf (mat) fibre-reinforced hexagonal composite tube. Various fibre contents were considered, including 25%, 30%, 35% and 40%. A fibre content of 25% to 30% (mass percent) demonstrated the best crashworthiness parameters. A high percentage of fibre loading 40% and more, due to poor bonding between the fibre and matrix, was not capable of transferring load to another, and hence stress was accumulated at certain points of the composite, which led to lower energy absorption mechanical properties. The reinforcing fibers are strong, stiff and effective for improving the mechanical properties of composite materials. However, reinforcing fibres are often brittle and abrasive, lack toughness, and can degrade chemically when exposed to the environment. A few distinct failure modes were identified during the experiments, including the progressive failure mode, in which failure begins at the top end of the tube, and the transverse crack failure mode, which is associated with the buckling failure mode. Phase two was devoted to study the static crushing behaviour of composite hexagonal tubes under uniform axial load. Three lengths of hexagonal composite tubes were tested 50, 100, and 150 mm with same hexagonal angle 45°. Results showed that tube with length 50 mm exhibits a high specific energy absorption as well as higher average crushing load. Phase three involved fabrication and testing of five different hexagonal tubes of reinforced natural kenaf (mat) with different angles from a range of 40ο to 60ο and in 5ο increments of the angle, to determine the effect of geometry on crashworthiness parameters of natural kenaf fibre reinforced composite hexagonal tubes. Results obtained in this phase show that the structures failed in a few distinct failure modes such as progressive failure mode and fragmentation failure associated with longitudinal cracks. The composite tube with β= 60ο exhibited a local buckling failure mode and displayed the highest specific energy absorption capability equal to 9.2 kJ/Kg. On the other hand, the new crashworthiness parameter was introduced as a catastrophic failure mode indicator (CFMI),the last phase was when the specimens were subjected to a lateral quasi-static compressive load. In this phase, the supporting plate was used inside the tube for the following reasons. The main purpose was to improve the energy absorbed by the tubes. The improvements, including the use of energy absorbing materials and structures in the plate inside the tubes, ensure more favourable decelerations during a crash/accident, resulting in fewer injuries to the car occupants. Furthermore, using a supporting plate inside the hexagonal tubes can control the load distribution during the crushing period and can diminish the structure weight. Three configurations of β=40ο, β=50ο and β=60ο of natural non-woven kenaf (mat)/epoxy were laminated. The effects of the hexagonal angles, supporting plate inside the tubes, and failure modes were studied by a lateral compression test. The crashworthiness of the tubes was evaluated by an analysis of the specific energy absorption in quasi-static lateral compression. Specific energy absorption was obtained from the load-displacement curve during testing. The failure mode of the tubes was analysed from high resolution photographs. Overall, the tube with β=40ο had the best crashworthiness among the tubes. Above all, the results showed that the tubes with supporting plates showed better specific energy absorption (SEA) for all tested specimens and exhibited approximately 69% better crashworthiness than the nonsupporting ones. The results also demonstrated that all specimens failed by the longitudinal failure mode.